Nusantara Pra Islam: Prediksi Masa Depan Islam di Indonesia - Santosa (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2021)
Looking at the historical flow of Islamic development in Indonesia as such, the author took an analysis that the future prospects of Islam in Indonesia have a great opportunity to continue to develop, be it in the fields of politics, economics, education, social, and culture. This can be seen from the history of Islam in Indonesia that continues to develop until now, this is the early stage of the emergence of awareness of the Indonesian nation of the importance of planting religious values in Indonesian society so that the Indonesian nation can meet the future not only with science and technology but also in the balance by IMTAQ. The era of globalization in the 21st century that has begun at this time, Islam in Indonesia has apparently exerted a huge influence on the advancement of Islam in the world. Although the existence of Islam today is really faced with a fairly severe challenge that requires the involvement of various parties concerned. With regard to this, strategic efforts need to be made, among others: by providing knowledge, skills, and piety in all fields (religious, political, economic, social, cultural, educational) so as to give birth to creative, innovative, independent and productive people considering the world to come is a competitive world.